Adaptive cognitive dimension and maladaptive behavioral dimension as motivating factors in school achievement - Zenuni, Anita; Vehapi, Shemsedin (AAB College, 2013)
This research examines a multi-dimensional model of student motivation and engagement. Through this model, the levels of development of factors that reflect increased motivation (adaptive dimensions) and those that reflect reduced motivation (maladaptive dimensions) among students are understood. The research was completed using the survey method, with student self-reporting answers in questionnaires on studied variables in their grades in schools. Research age group for this study was 200 students of Grades 10, 11 and 12 from public upper secondary school “Sami Frashëri” and students of private upper secondary school “Luarasi” in Prishtina. Selection of this sample utilized convenience method. Data were analyzed using SPSS 18.0 statistical package for social sciences. The study found that adaptive cognitive dimension has positive effects on student school achievement and that maladaptive behavioral dimension has negative effects. The research also found that these two factors are significant in student achievement for this age group. The research may serve as a good orientation base for explaining the complex nature of relations of various factors with school achievement. The purpose of this research is to understand that both motivational factors (protecting factors) and demotivating factors (risk factors) are important for student school achievement. Another purpose is to understand levels of development of factors that reflect increased motivation and those that reflect reduced motivation.